The Influence of Project-Based Learning on Speaking Skills: A Case Study of Political Science Students in Presenting SDGs Campaign - Akbar Mandala Arya Putra; Agustinus Hardi Prasetyo (Journal of Education and Teaching (JET), 2025)
This study aims to analyze the effect of Project-Based Learning (PBL) on the public speaking skills of Political Science students in the context of Sustainable Development Goals (SDGs) campaign presentations. The background of this study is based on the need to improve the oral communication skills of non-English language students through a contextual and meaningful learning approach. The study used a quantitative survey method involving 130 first-semester students taking English courses. The research instrument was a questionnaire tested for validity and reliability, and the data were analyzed using simple linear regression. The analysis showed that PBL significantly affected public speaking skills, with a contribution of 50.8% (r = 0.713; p < 0.001). The constructivist theory, which emphasizes experience and active learning, is supported by this data. Students are given an authentic context that promotes improved confidence, fluency, and communication structure when SDG subjects are incorporated into learning projects. This study recommends using PBL in various non-English language study programs to develop academic speaking skills relevant to global issues.